Pengaruh Stres Kerja Dan Pemberdayaan Terhadap Kepuasan Kerja Karyawan Di Prama Hotel - Pratama, Ida Bagus Winastya; Sriathi, Anak Agung Ayu (E-Jurnal Manajemen; Vol 4 No 11 (2015), 2015)
The purpose of this study was to examine 1) the effect of work stress on employee job satisfaction. 2) the effect of employee empowerment on employee job satisfaction. This research was conducted in the department of food and beverage in Prama Sanur Beach Hotel, samples taken by 56 people. Data collection is done by observation, questionnaires, and interviews. The analysis technique used is multiple linear regression and t test. Results of the data analysis showed that work stress variables significant negative effect on job satisfaction, employee empowerment while variable positive and significant impact on job satisfaction. Suggestions of this study,the employee should be given employment in accordance with the duties and functions of each and employees fairly sizeable giventhe opportunity to be involved in the work.
Keywords: kepuasan kerja; stres kerja; pemberdayaan karyawan